2021
DOI: 10.1371/journal.pone.0251010
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of catheter-related bloodstream infections in neutropenic oncohematological patients

Abstract: Background We aimed to describe the epidemiology of catheter-related bloodstream infections (CRBSIs) in onco-hematological neutropenic patients during a 25-year study period, to evaluate the risk factors for Gram-negative bacilli (GNB) CRBSI, as well as rates of inappropriate empirical antibiotic treatments (IEAT) and mortality. Materials/Methods All consecutive episodes of CRBSIs were prospectively collected (1994–2018). Changing epidemiology was evaluated comparing five-year time spans. A multivariate regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 33 publications
(43 reference statements)
4
20
0
Order By: Relevance
“…However, there is only limited data exploring the incidence of CRBSI in patients who undergo catheter insertion in the ED. Although we could not collect detailed clinical data, such as the severity of the acute illness, speci c diagnosis, and indications of central line catheterization, the incidence of CRBSI was quite similar to that reported by previous research 12,13 . Additionally, the risk factors for occurring CRBSI, including age, TPN, hemodialysis, and repeated trials, have also been cited in the literature 14,15 .…”
Section: Discussionsupporting
confidence: 74%
“…However, there is only limited data exploring the incidence of CRBSI in patients who undergo catheter insertion in the ED. Although we could not collect detailed clinical data, such as the severity of the acute illness, speci c diagnosis, and indications of central line catheterization, the incidence of CRBSI was quite similar to that reported by previous research 12,13 . Additionally, the risk factors for occurring CRBSI, including age, TPN, hemodialysis, and repeated trials, have also been cited in the literature 14,15 .…”
Section: Discussionsupporting
confidence: 74%
“…Soriano et al have identified Acinetobacter baumanii as the main causative microorganism, followed by S. epidermidis and Candida albicans [20]. One prospective study in Poland has found an increase in Gram negative bacteria and Candida among neutropenic patients with CLABSI [24]. Recently, bloodstream infection caused by Candida species has also become a concerning trend in China.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, skin colonizers gram-positive microorganisms – mostly Coagulase-negative Staphylococci and S. aureus – have been the leading cause of CRBSI, whereas Gram-negative pathogens causing CRBSI have been mainly described in outbreak scenarios and in special populations such as spinal cord injuries, femoral catheters, oncohaematological diseases, gastrointestinal colonization or prolonged admission in the ICU [3,6,7]. However, in latest years, GNB have been estimated to be the cause of 20–25% of the cases of CRBSI [4 ▪ ,8,9], with some studies reporting even a predominance of GNB [10]. It has been hypothesized that the increasing complexity of hospitalized patients, longer hospitalizations, widespread use of broad-spectrum antibiotics or the implementation of preventive measures specifically targeted at Gram-positive organisms may be the reasons behind this epidemiological shift.…”
Section: Gram-negative Bacilli As An Emerging Cause Of Gram-negative ...mentioning
confidence: 99%
“…Gram-negative bacilli (GNB) constitute an emerging cause of CRBSI [3] and concerns regarding these potentially multidrug-resistant (MDR) infections have generated the need for optimizing its management. Indeed, inappropriate empirical treatment has been frequently described in GNB-CRBSI probably due to low suspicion of the clinicians, which inevitably leads to a delay in the initiation of specific antimicrobial treatment and therefore worst outcomes [4 ▪ ,5].…”
Section: Introductionmentioning
confidence: 99%